An introduction to bioreactor hydrodynamics and gas-liquid mass transfer - Kadic, Enes, 1973- (Wiley, 2014)
"This book reviews and compares the major types of bioreactors used to produce renewable fuels, chemicals, medicines, and proteins, by providing an overview of the hydrodynamics and gas-liquid mass transfer operations in this equipment. These operations are important because they influence the quality and quantity of the desired material produced in the reactor. The text also discusses advantages and disadvantages of each bioreactor and provides a procedure for optimal bioreactor selection based on current process needs, giving chemical and mechanical engineers a practical, working reference"--